PERSEPSI MAHASISWA AKUNTANSI TERHADAP ETIKA PENYUSUNAN LAPORAN KEUANGAN SYARI’AH SESUAI PSAK No. 101 - Siregar, Wasilaturahmi; Hidayah, Khusnul (Jurnal REKSA: Rekayasa Keuangan, Syariah dan Audit, 2013)
This research to determine differences in accounting students perceptions of the ethics financial shari’ah statement in accordance with SFAS No. 101. The analysis was based on respondents answers were obtained through questionnaires distributed at Private Colleges and Universities Public Islam. Population of this study is that accounting students are in Private Colleges and Universities Public Islam. This study uses purposive sampling method. Samples were taken from six semesters of accounting students and eight who have taken courses Accounting Theory. To test the validity of the data used Pearson correlation, to test the reliability of the data used Cronbach Alpha while the data used to test the normality Kolmogorov-Smirnov, and the data used to test for differences Independent samples t-test. The results are hypothesis 1, hypothesis 2, hypothesis 4, and 5 are acceptable hypothesis that there are differences in the perception of earnings management, misstatements in the financial statements, cost-benefit, and responsibility to the users of financial statements Shariah between accounting students at university Private Higher Islam and Higher Education General. And hypothesis 3 was rejected, ie there is no difference between the perceptions of disclosure of accounting students in Private Colleges and Universities Public Islam.